Strategies for Pharmacological Organoprotection during Extracorporeal Circulation Targeting Ischemia-Reperfusion Injury - Salameh, Aida; Dhein, Stefan (Frontiers in Pharmacology, 2015)
Surgical correction of congenital cardiac malformations or aortocoronary bypass surgery in many cases implies the use of cardiopulmonary-bypass (CPB). However, a possible negative impact of CPB on internal organs such as brain, kidney, lung and liver cannot be neglected. In general, CPB initiates a systemic inflammatory response (SIRS) which is presumably caused by contact of blood components with the surface of CPB tubing. Moreover, during CPB the heart typically undergoes a period of cold ischemia, and the other peripheral organs a global low flow hypoperfusion. As a result, a plethora of pro-inflammatory mediators and cytokines is released activating different biochemical pathways, which finally may result in the occurrence of microthrombosis, microemboli, in depletion of coagulation factors and haemorrhagic diathesis besides typical ischemia-reperfusion injuries. In our review we will focus on possible pharmacological interventions in patients to decrease negative effects of CPB and to improve post-operative outcome with regard to heart and other organs like brain, kidney or lung.